Spatial Difference of China’s Regional Logistics Development and Construction of Information Network Platform Based on Artificial Intelligence Technology Under the Background of New Economy - Zhao, Shajunyi; Xie, Cuijie (Frontiers in Psychology, 2022)
Regional logistics is an important part of regional economy. It plays an important role in optimizing the allocation of regional resources, promoting the upgrading of regional industrial structure and promoting the sustainable development of regional economy. It is known as the "accelerator" of regional economic growth. Under the background of the expanding regional economic differences in China, this paper focuses on the important components of regional economy, research on regional logistics in different regions. This paper focuses on the regional logistics development level, the internal mechanism of regional logistics promoting regional economic growth, the current situation and influencing factors of regional logistics development level differences, and the regional logistics development level differences. The purpose of this paper is to study the application of artificial intelligence technology to the spatial difference analysis of China's regional logistics development and the construction of information network platform under the background of new economy. In this paper, factor analysis is used to construct the index system. This paper comprehensively analyzes the spatial differences of China's regional logistics development under the background of new economy from two aspects of single factor index and multi factor index. By calculating the Gini coefficient and entropy of regional logistics, this paper analyzes the spatial difference of China's regional logistics development and the construction of information network platform under the background of new economy. The research shows that the intensity of regional logistics connection is significantly enhanced, the regional logistics network is further improved, and a relatively complete multi-level regional logistics network structure is basically formed. In addition, there are great differences in the level of logistics development among regions. The characteristics of the spatial distribution circle in the eastern, central and western regions are obvious, which is positively related to the economic development, and is the Pearl with the strongest comprehensive competitiveness.